PREVALENCE OF MICROALBUMINURIA IN CHILDREN AND ADOLESCENTS WITH DIABETES MELLITUS TYPE I - H. Moayeri H. Dalili (Acta Medica Iranica, 2006)
Persistent microalbuminuria is predictive of nephropathy in patients with type I diabetes mellitus (DM) and has led to the development of screening programs and intervention studies. We report a longitudinal evaluation of urinary albumin excretion in 118 children with type I DM, attending a single clinic over a period of seven years. Collected blood and urine samples were analyzed for glycated hemoglobin (Hb A1c), cholesterol, triglyceride (TG), creatinine and for 12 h urinary albumin and creatinine concentrations. Blood pressures were recorded and clinical data collected. Twenty– three (19.5%) children had persistent microalbuminuria (urine albumin 30-300 mg/24 h) on at least three consecutive occasions. Factors associated with microalbuminuria in diabetic children included longer duration of DM, higher mean age, higher mean Hb A1c, higher mean arterial blood pressure and higher cholesterol and TG levels (P < 0.001). Significantly more girls than boys and more pubertal and post pubertal patients had microalbuminuria but one patient developed microalbuminuria under the age of 11 years. In conclusion, microalbuminuria may appear as early as the prepubertal period, suggesting that metabolic control of DM is an important factor of diabetic nephropathy.